(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This study aimed at investigating the level of the psychological resilience, the level of with alexithymia, the relationship between the psychological resilience and alexithymia for the fourth-year students in of education faculty – Lattakia university. Descriptive approach was used. The sample consists of (161) the fourth-year students from dept. of Class teachers. Two scales were distributed to the sample (Tornoto; TAS-20 and CD-RISC). The results showed: Students have moderate level of psychological resilience where the percentile weight of the average is (58.78%) on the scale of the psychological resilience. Students also have moderate of alexithymia where the percentile weight of the average is (54.21%) on the scale of the alexithymia. There is a negative statistically significant relationship between alexithymia the psychological resilience. The research introduced many suggestions which are: giving psychological resilience more importance, organizing general lectures about alexithymia and psychological resilience and encourage students to express their feelings freely without fear or shyness.